EFFECTIVENESS OF LITERATURE CIRCLES ON STUDENTS’ READING COMPREHENSION - Dini Irawati (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2016)
This study reports an experimental study to see the effect of literatures circles to improve reading comprehension of English department students of  State Islamic Institute (IAIN) of Samarinda. A quasi experimental research using nonrandomized control group pretest-posttest design was conducted to see effectiveness of literature circles on students’ reading comprehension. A number of 24 students were taken as sample from the first semester students joining in an intensive English course program in  academic year 2011/2012. Using independent t-test, the analysis of the posttest means the finding yielded a t-value of 3.11. The t-value (3.11) is higher than the critical table 1.678 at p=.05 and df=44 (one-tailed).  The result evidently shows that literature circles contribute a significant effect to improve students’ reading comprehension.